Thiophene-2,5-dicarboxylic acid bis-aryl(alkyl) amides - Koparir, M; Cansiz, A; Çetin, A (John Wiley & Sons Inc, 2005)
A base-catalyzed condensation of diacetamido sulfides [(RNHCOCH2)(2)S)] with glyoxal affording thiophene-2,5-dicarboxylic acid bis-aryl(alkyl)amides has been accomplished under mild conditions. Excellent results were readily obtained when R was a substituted 3-nitrophenyl, 4-nitrophenyl, 4-chlorophenyl group, but the yield was poor when R was cyclohexyl. Unknown compounds were characterized by elemental analyses, IR, H-1, and C-13 NMR techniques. (c) 2005 Wiley Periodicals, Inc.
Keywords: Hinsberg-Reaction; Facile Synthesis; Diketo Sulfides; 2,5-Diacylthiophenes